Saturation levels of mobile telecommunications markets and optimal termination rates - Ventosa-Santaulària, Daniel; Elbittar, Alexander; Matías, Pedro; Aguilar Huerta, Carlos (Estudios Económicos de El Colegio de México, 2020)
This paper analyzes the how the two main mobile telecommunication payment regimes, receiving party pays (RPP) and calling party pays (CPP), impact mobile telecommunication diﬀusion patterns; and provides evidence that a quadratic and concave relationship exists between mobile termination rate and the level of penetration of mobile telecommunications. We also ﬁnd signiﬁcant evidence that competition, political regime and internet use aﬀect the saturation rate as well. Finally, we ﬁnd that the global behavior of telecommunication markets has contributed to a reduction in the gap between the optimal and actual mobile termination rates in most countries.